Sporomusa ovata as Catalyst for Bioelectrochemical Carbon Dioxide Reduction: A Review Across Disciplines From Microbiology to Process Engineering - Madjarov, Joana; Soares, Ricardo; Paquete, Catarina M.; Louro, Ricardo O. (Frontiers in Microbiology, 2022)
Sporomusa ovata (S. ovata) is a bacterium that can accept electrons from cathodes to drive microbial electrosynthesis (MES) of acetate from carbon dioxide (CO2). It is the biocatalyst with the highest acetate production rate described. Here we review the research on S. ovata across different disciplines, including microbiology, biochemistry, engineering, and materials science, to summarize and assess the state-of-the-art. The improvement of the biocatalytic capacity of S. ovata in the last ten years, using different optimization strategies is described and discussed. In addition, we propose possible electron uptake routes derived from genetic and experimental data described in literature and point out the possibilities to understand and improve the performance of S. ovata through genetic engineering. Finally, we identify current knowledge gaps guiding further research efforts to explore this promising organism for the MES field.